O-GlcNAc Modification: Friend or Foe in Diabetic Cardiovascular Disease - Karunakaran, Udayakumar (Korean Diabetes Association, 2010)
O-Linked β-N-acetyl glucosaminylation (O-GlcNAcylation) is a dynamic post-translational modification that occurs on serine and threonine residues of cytosolic and nuclear proteins in all cell types, including those involved in the cardiovascular system. O-GlcNAcylation is thought to act in a manner analogous to protein phosphorylation. O-GlcNAcylation rapidly cycles on/off proteins in a time scale similar to that for phosphorylation/dephosphorylation of proteins. Several studies indicate that O-GlcNAc might induce nuclear localization of some transcription factors and may affect their DNA binding activities. However, at the cellular level, it has been shown that O-GlcNAc levels increase in response to stress and augmentation of this response suppresses cell survival. Increased levels of O-GlcNAc have been implicated as a pathogenic contributor to glucose toxicity and insulin resistance, which are major hallmarks of type 2 diabetes and diabetes-related cardiovascular complications. Thus, O-GlcNAc and its metabolic functions are not yet well-understood; focusing on the role of O-GlcNAc in the cardiovascular system is a viable target for biomedical investigation. In this review, we summarize our current understanding of the role of O-GlcNAc on the regulation of cell function and survival in the cardiovascular system.